The Role of Talent Management In Stimulating Human Resources Career Development - Rachmawati, Meida; Yochanan, Elisha; Heriyanto, Heriyanto; Prastyo, Yudo (Green Publisher Indonesia, 2023)
Amidst the competition between companies today, creating a competitive advantage is an absolute thing that organizations must fulfill. One way to create excellence is to have employees with the skills, knowledge, and competencies that meet your organization’s needs. Human Resources (HR) is one of the resources that play an important role in achieving the goals of an organization. While an organization has sufficient physical capital or the latest technology, people will still manage and nurture the implementation. The study uses quantitative methods to analyze the extent to which talent management impacts career development in HR organizations. A private university in LLDikti Region VI has shown a partial and simultaneous positive and significant influence on aptitude management, knowledge management, and job evaluation in employee career development. The existence of good talent management in the organization is expected to increase the potential talents within the organization to occupy crucial positions in developing the organization in a better direction